34th Annual Frontiers in Education, 2004. FIE 2004.
DOI: 10.1109/fie.2004.1408756
|View full text |Cite
|
Sign up to set email alerts
|

Developing collaborative tools to promote communication and active learning in academia

Abstract: Groupware applications such as AOL's Instant Messenger and Microsoft's NetMeeting have been growing in popularity in the general public for many years, starting with students on college campuses and more recently gaining acceptance in the business world as effective tools to aid in communication and productivity. Although many of these technologies were first popularized on college campuses, their use has yet to be integrated into the student/instructor teaching relationship, remaining more widely used between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…While half 50.67 % (189) of the respondents revealed that modern social media platforms have led to closed ethnic groups which make it difficult to others not belonging to that cultural group.Lastly, some students 17.96 % (67) indicated that all students are not in social media group hence leading to discrimination of students who do not fall in any group especially those who are broke. From the findings, as supported by Frees and Kessler (2004), technology based platforms are potential means to bring students together,including the enhancement of academic goals. Above it has been explained that such platforms make communication easier among students and even students with their lecturers and administrators (Nicholson, 2002).…”
Section: Figure 1: Contribution Of Modern Social Network In Buildingmentioning
confidence: 89%
“…While half 50.67 % (189) of the respondents revealed that modern social media platforms have led to closed ethnic groups which make it difficult to others not belonging to that cultural group.Lastly, some students 17.96 % (67) indicated that all students are not in social media group hence leading to discrimination of students who do not fall in any group especially those who are broke. From the findings, as supported by Frees and Kessler (2004), technology based platforms are potential means to bring students together,including the enhancement of academic goals. Above it has been explained that such platforms make communication easier among students and even students with their lecturers and administrators (Nicholson, 2002).…”
Section: Figure 1: Contribution Of Modern Social Network In Buildingmentioning
confidence: 89%
“…Within the distance learning community, research-ers have described the use of technology for collaborative writing, with mention of tools such as email, chatting, shared sites, individual word processors, and web conferencing for joint writing projects (10,11,12,13,14). And while Frees and Kessler [15] introduce a desktop sharing component into an introductory computer science programming course, and computer programmers regularly work remotely using such tools as Squad [16], we have not been able to find any reference to the specific use of desktop sharing for the teaching of academic writing and the ongoing development in student writers of redrafting and editing strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Office hours have long existed as a tool to provide instructor-student interaction, and to help students ask their questions outside of the class timeframe. In large-size college classes, using emails and online office hours have been introduced as effective substitutions for face-to-face office hours [1][2][3][4]. Moreover, cooperative learning has repeatedly proven to have positive impacts on students' educational experience [3,5].…”
Section: Wip: Mandatory Attendance In Office Hours To Improve Students' Learning Experience Introductionmentioning
confidence: 99%
“…In large-size college classes, using emails and online office hours have been introduced as effective substitutions for face-to-face office hours [1][2][3][4]. Moreover, cooperative learning has repeatedly proven to have positive impacts on students' educational experience [3,5]. Cooperative learning, which can be incorporated in classes of any size, enables students to improve their social and team-working skills.…”
Section: Wip: Mandatory Attendance In Office Hours To Improve Students' Learning Experience Introductionmentioning
confidence: 99%